2021
DOI: 10.1186/s40691-021-00273-6
|View full text |Cite
|
Sign up to set email alerts
|

Charaterizations of 3D printed re-entrant pattern/aramid knit composite prepared by various tilting angles

Abstract: This study intended to compare and analyze the Poisson's ratio and mechanical properties of aramid knit (ARNT), 3D printed auxetic re-entrant pattern (3DP-RE), and 2 types of composite fabrics manufactured with ARNT and 3DP-RE. Specimens were manufactured by 3D printing the re-entrant pattern with a CFDM (conveyor fused deposition modeling) 3D printer and TPU (thermoplastic polyurethane) filament, combining with aramid knit in 2 ways. Then, Poisson's ratio, bending, compression, and tensile properties were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In terms of bending properties, the test was conducted according to the methods used in previous studies [10,12]. Figure 2 shows the universal mechanical testing machine (AGS-X, Shimadzu Co. Ltd., Kyoto, Japan) used to carry out the bending test to determine the bending characteristics of FA and UA samples with various thicknesses.…”
Section: Mechanical Properties Of 3d-printed Humanoid Robot Arm With ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of bending properties, the test was conducted according to the methods used in previous studies [10,12]. Figure 2 shows the universal mechanical testing machine (AGS-X, Shimadzu Co. Ltd., Kyoto, Japan) used to carry out the bending test to determine the bending characteristics of FA and UA samples with various thicknesses.…”
Section: Mechanical Properties Of 3d-printed Humanoid Robot Arm With ...mentioning
confidence: 99%
“…In an auxetic structure, deformation starts from one cell, which is followed by the cells in the particular row [7][8][9]. The energy absorption properties of auxetic materials are excellent as the structure causes the material to swell when compressed, withstanding the load applied [10]. Due to their unique properties, they have found applications in industries like fashion, aerospace, automotive, sports, medical textiles, footwear, and architecture [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Imjoo Jung et al compared the two types of fabric composites—aramid knit (ARNT) and 3D printed auxetic re‐entrant pattern (3DP‐RE) with the help of CFDM (conveyor FDM). Thus by comparing the mechanical properties it discovered that the 3DP‐RE/ARNT composite fabric have excellent properties 93 …”
Section: Thermoplastic Polyurethanementioning
confidence: 99%
“…Imjoo Jung et al compared the two types of fabric compositesaramid knit (ARNT) and 3D printed auxetic re-entrant pattern (3DP-RE) with the help of CFDM (conveyor FDM). Thus by comparing the mechanical properties it discovered that the 3DP-RE/ARNT composite fabric have excellent properties 93. Jiacheng Ji et al incorporate the different types of materials like carbon fibers/alumina/silicon rubber and so forth in TPU to check the thermal conductivity of the polymer product.…”
mentioning
confidence: 99%
“…Similarly, Takahashi and Kim 26 fabricated a soft and flexible textile by considering bending properties with the use of an FDM 3D printer. Jung et al 27 concluded that the compression strength and toughness of 3D printed auxetic re-entrant pattern/textile composite fabrics are excellent when compared to those of the substrate fabric. Furthermore, Eom et al 28 analyzed the thermal properties of 3D printed TPU with different 3D structures.…”
Section: Introductionmentioning
confidence: 99%